2020
DOI: 10.1016/j.drugalcdep.2019.107820
|View full text |Cite
|
Sign up to set email alerts
|

Greater delay discounting and cannabis coping motives are associated with more frequent cannabis use in a large sample of adult cannabis users

Abstract: Background: Self-regulation deficits expressed through a decreased ability to value future rewards (delay discounting (DD)) and impaired emotion regulation (negative urgency (NU), cannabis coping motives (CCM), and anxiety sensitivity (AS)) relate to more frequent or problematic cannabis use. However, there is a need to better understand how self-regulation and emotion regulation constructs reflect competition between deliberative and reactive systems that drive individual differences in cannabis use patterns.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 71 publications
1
18
0
Order By: Relevance
“…Furthermore, daily users were more impulsive than occasional users in that they discounted future rewards more steeply. This finding was consistent with a study by Sofis et al (2020) in which the authors also classified participants based on frequency of use, and found the same pattern wherein greater frequency of use was associated with greater delay discounting. In the broader literature on addictive behaviors, various substance-use variables have been shown to be associated with greater delay discounting, including severity, dependence, and quantity/frequency (MacKillop et al, 2011;Amlung, Vedelago, Acker, Balodis, & MacKillop, 2017).…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, daily users were more impulsive than occasional users in that they discounted future rewards more steeply. This finding was consistent with a study by Sofis et al (2020) in which the authors also classified participants based on frequency of use, and found the same pattern wherein greater frequency of use was associated with greater delay discounting. In the broader literature on addictive behaviors, various substance-use variables have been shown to be associated with greater delay discounting, including severity, dependence, and quantity/frequency (MacKillop et al, 2011;Amlung, Vedelago, Acker, Balodis, & MacKillop, 2017).…”
Section: Discussionsupporting
confidence: 90%
“…This index of the preference for smaller sooner over larger later rewards is of high conceptual relevance to SUD research, as it closely resembles behavior observed in individuals with SUDs, i.e., choosing immediate drug effects over long-term goals (e.g., taking care of family or school/job etc.). Empirically, higher delay discounting in individuals with SUDs [ 25 ] and associations of delay discounting with substance use frequency [ 26 ] and SUD severity (indicating substance-related problems) are consistently observed [ 27 29 ]. Delay discounting correlates with premeditation [ 19 , 30 32 ], but also urgency [ 30 ] and sensation seeking [ 32 ], but a meta-analysis suggests that these associations are overall rather weak [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…These differences among studies may be influenced by variations in cannabis use among samples. Greater frequency of cannabis use (Sofis et al, 2020 ), greater substance use symptom severity (Stea et al, 2011 ; Strickland et al, 2017 ) and earlier age of onset of use (Kollins, 2003 ; Heinz et al, 2013 ) have been associated with increased discounting rates among cannabis users. The PRLT is an operant learning paradigm in which participants make repeated choices between two stimuli on each trial, with immediate feedback (e.g., a gain or loss of points) determined probabilistically (e.g., the “correct” and “incorrect” stimuli may result in a gain of points only 80 or 20% of the time, respectively) (Cools et al, 2002 ).…”
Section: Introductionmentioning
confidence: 99%
“…Population samples indicate that persons with cannabis dependence have very high lifetime rates of psychiatric comorbidity, approaching 90% (Agosti et al, 2002 ), which may contribute to decision making deficits. However, studies of decision making in cannabis users often have not assessed or excluded subjects for lifetime history of psychiatric disorders, as in previous studies of delay discounting in that population (Stea et al, 2011 ; Boggs et al, 2012 ; Heinz et al, 2013 ; Peters et al, 2013 ; Lee et al, 2015 ; Aston et al, 2016 ; Strickland et al, 2017 ; Jarmolowicz et al, 2020 ; Sofis et al, 2020 ). A second issue in studies of discounting rates is lack of urinalysis screening for illicit drug use in cannabis users to rule out other substance use and, in control participants, to confirm self-reported abstinence from cannabis or illicit substances (Johnson et al, 2010 ; Stea et al, 2011 ; Heinz et al, 2013 ; Peters et al, 2013 ; Strickland et al, 2017 ; Jarmolowicz et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%